COMPARISON OF PAIN SCORE AND POSTOPERATIVE ANALGESIC REQUIREMENT IN PATIENTS UNDERGOING CAESAREAN SECTION WITH & WITHOUT PERI INCISIONAL LOCAL ANESTHESIA - Sumara Tabssam; Robina Firdous (Journal of University Medical & Dental College, 2014)
ABSTRACT: OBJECTIVES: To determine the mean pain score and postoperative mean analgesic requirement after periincisional infiltration of local anaesthesia in patients undergoing caesarean section versus control group. STUDY DESIGN: Randomized control trial. PLACE AND DURATION OF STUDY: Punjab Medical College/Allied and DHQ Hospitals Faisalabad, from July 2012 to February 2013. METHODOLOGY: In order to compare two techniques 142 patients were divided into two groups i.e control group A (receiving peri-incisional infiltration of 20 ml of normal saline) and experimental group B (receiving peri-incisional infiltration of 20 ml of 0.5% bupivacaine). Pain score was noted in post operative period at 12 hours. Total amount of intravenous tramadol given was also noted. Statistical analysis was performed to compare results. RESULTS: Mean pain score of group A (4.37 ± 1.124) and of group B (4.31 ± 0.935) showed no significant difference (p>0.05) at 12 hour. But a significant difference (p <0.05) was seen in total amount of analgesia consumed up to 12 hours in group A (104.23 ± 34.586) and B (76.06 ± 32.579). CONCLUSION: After caesarean delivery, use of peri-incisional local anesthesia have no effect on pain score at 12 hours but results in less intravenous analgesia requirement as compared to controls.